2007
DOI: 10.1111/j.1528-3585.2007.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Nationalism and Adaptation in Cyprus

Abstract: Both ethnic communities in Cyprus have maintained strong political and cultural ties with Greece and Turkey, respectively, and at some point of their twentieth century history, each has aspired to become part of either the former or the latter. Yet the way this relationship has been imagined has differed across time, space, and class. Both communities have adapted their identities to prevailing ideological waves as well as political opportunities, domestic alliances, and interests. The article evaluates differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 18 publications
0
53
0
3
Order By: Relevance
“…Loizides (2007: 185), drawing on Laitin's (1998) analysis, argues that the ‘case of Cyprus supports scholarly perspectives that see identities as constructed and reconstructed as political factors and opportunities change’. From this perspective, Cypriot identity is both contingent and contextual.…”
Section: Banal Europeanism: Diversity As a Source Of Integrationmentioning
confidence: 98%
See 2 more Smart Citations
“…Loizides (2007: 185), drawing on Laitin's (1998) analysis, argues that the ‘case of Cyprus supports scholarly perspectives that see identities as constructed and reconstructed as political factors and opportunities change’. From this perspective, Cypriot identity is both contingent and contextual.…”
Section: Banal Europeanism: Diversity As a Source Of Integrationmentioning
confidence: 98%
“…Although these appropriate symbols and rhetoric from both mainland nationalism and from Cypriotism, they pay ‘more attention to the aspirations of the ethnic community in the island than to the interest of the ‘national centers’ or Cyprus as a whole. Thus, Greek Cypriotism and Turkish Cypriotism take ascendancy in two respective frequently oppositional camps’ (Loizides 2007: 173).…”
Section: Banal Europeanism: Diversity As a Source Of Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the adults that the children come into contact with on a daily basis within family networks are also likely to present much messier memories reflecting their varying personal experiences and previous or current ideological positioning. For example, Loizides () argues that nationalist discourses often reflect right/left wing ideologies within the two main communities with the left more likely to challenge the selective amnesia of both sides. At times, during the focus group discussions, some young people suggested that more nuanced presentations of history were recounted by family members as the following quote indicates:
Of course I think both sides say different stories but my grandmother says it is so hard and both sides made bad things happen to each other and we each need to remember this.
…”
Section: Accepting Challenging and Transforming Memoriesmentioning
confidence: 99%
“…The literature on the Cyprus conflict can be classified into two in terms of internal and external dynamics. Whereas some studies focused primarily on the internal dynamics of the Cyprus conflict (Kelman, 1990;Hadjipavlou-Trigeorgis,1993;Diamond and Fisher, 1995;Yılmaz, 2004;Loizides, 2007;Husnu and Crisp, 2010), the others dealt predominantly with the external aspects of the conflict (Keashly and Fisher, 1990;Richmond, 1999;Fisher, 2001;Güney, 2004;Müftüler-Bac and Güney, 2005;Eralp and Beriker, 2005).…”
Section: Introductionmentioning
confidence: 99%